Quantitative Separation of Tremor and Ataxia in Essential Tremor. Issue 2 (8th July 2020) - Casamento‐Moran, Agostina; Yacoubi, Basma; Wilkes, Bradley J.; Hess, Christopher W.; Foote, Kelly D.; Okun, Michael S.; Wagle Shukla, Aparna; Vaillancourt, David E.; Christou, Evangelos A.
Abstract : Objective: This study addresses an important problem in neurology, distinguishing tremor and ataxia using quantitative methods. Specifically, we aimed to quantitatively separate dysmetria, a cardinal sign of ataxia, from tremor in essential tremor (ET). Methods: In Experiment 1, we compared 19 participants diagnosed with ET undergoing thalamic deep brain stimulation (DBS; ETDBS ) to 19 healthy controls (HC). We quantified tremor during postural tasks using accelerometry and dysmetria with fast, reverse‐at‐target goal‐directed movements. To ensure that endpoint accuracy was unaffected by tremor, we quantified dysmetria in selected trials manifesting a smooth trajectory to the endpoint. Finally, we manipulated tremor amplitude by switching DBS ON and OFF to examine its effect on dysmetria. In Experiment 2, we compared 10 ET participants with 10 HC to determine whether we could identify and distinguish dysmetria from tremor in non‐DBS ET. Results: Three findings suggest that we can quantify dysmetria independently of tremor in ET. First, ETDBS and ET exhibited greater dysmetria than HC and dysmetria did not correlate with tremor ( R 2  < 0.01). Second, even for trials with tremor‐free trajectories to the target, ET exhibited greater dysmetria than HC ( p < 0.01). Third, activating DBS reduced tremor ( p < 0.01) but had no effect on dysmetria ( p > 0.2). Interpretation: We demonstrate that dysmetria can be quantified independently of tremor using fast, reverse‐at‐target goal‐directed movements. These results have important implications for the understanding of ET and other cerebellar and tremor disorders. Future research should examine the neurophysiological mechanisms underlying each symptom and characterize their independent contribution to disability. ANN NEUROL 2020;88:375–387.